Analisis Konten Aqidah pada Poster Digital di Akun Instagram @Mudaberdakwah - Maulida Zakiyah; Dewi Anggrayni; Ikhwan Hamdani (Institut Agama Islam Nasional Laa Roiba Bogor, 2022)
The development of Technology and Information which is now increasingly sophisticated and growing rapidly so that people are required to be able to choose and determine the information needed or information that is more universal or comprehensive. itself, several social media sites have been introduced and become popular all over the world. These types of social media are Facebook, Twitter, Youtube, Linkedin, Instagram, Whatsapp, etc. Each social media certainly has its own purpose for its users to share their experiences, ideas, or life moments. Instagram is the social media most interested in by the Indonesian people, number 2 after Facebook, the largest number of Instagram users in Asia Pacific. Seeing from the side of the advantages of Instagram, it returns to the user when using Instagram with positive things, of course the information that will be received will be positive, but it is another thing if the user uses Instagram media with negative things, the things he will receive will be negative. That's why people need to use this media properly and appropriately. Da'wah accounts are also popping up on Instagram. Spreading Islamic religious messages is packaged very attractively in order to attract modern society, because with a new place to preach, now Instagram social media can be a promising target or target. Because of that, not a few people have come to know and learn about the religion of Islam with these da'wah accounts on Instagram. Da'wah packaged in the form of digital posters can be called da'wah which aims to convey information or messages packaged through social media, besides that also related to making or choosing signs and arranging them in the form of images to convey an idea, one of the results is a poster or leaflet where the poster is a medium that can make everyone interested also does not require a lot of money. large and also fast and efficient in conveying an idea and a message of kindness.